Present Status of Organic Sheep Production in Ramgoti Upazila of Lakshmipur District - Sarker, AK; Amin, MR; Hossain, MA; Ali, MS; Hashem, MA (Journal of Environmental Science and Natural Resources, 2018)
The experiment was conducted to investigate the present status and potentialities of organic sheep production in Lakshmipur district of Bangladesh. Data were collected through an interview schedule personally from 30 respondents in 3 villages of Ramgoti Upazila who were involved in sheep production. Parameter studied were origin, feeds and fodder, breeding, health care, living condition of livestock and factors related to organic sheep production. All sheep was indigenous. 60 per cent farmers used roadside grass and 40% cultivated and roadside grass. Most of the farmers used mixed feed which was bought from local market and 17% farmers used vitamin mineral supplementation. All farmers used natural breeding. About 80, 80 and 83% farmers practiced vaccination, de-worming and grooming, respectively. About 13% farmers used hormone, antibiotic and growth promoter and only 33% farmers remove sick or injured animal from healthy stock. All farmers allowed access to outdoor and pasturing during winter season and none reared male and female sheep separately. Farmers did not keep and kept their livestock record were 90 and 10%, respectively. Most of the farmers were middle aged categories (53%) and education level of farmers of primary, secondary and higher secondary were 63, 30 and 7%, respectively. J. Environ. Sci. & Natural Resources, 10(2): 95-103 2017